Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3354/meps10008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the bioturbating lugworm Arenicola marina on the structure of benthic protistan communities

Abstract: Sedimentary coastal ecosystems like the European Wadden Sea in the northeasternAtlantic harbor large populations of burrowing infauna, such as arenicolide polychaetes. These 'ecosystem engineering' macrofaunal organisms destabilize sediments by reworking and irrigating them, leading to a reorganization of sediment physicochemical state and bacterial communities. Here, we tested the effects of the lugworm Arenicola marina on intertidal psammophilic protistan community diversity and structure in a field experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Only one previous study has assessed microbial eukaryote diversity in polychaete burrows (Engel et al ., ). Engel and colleagues () showed that ciliates and diatoms dominate A. marina burrows in non‐polluted coastal sediment. In this study, fungi dominated both H. diversicolor burrow and un‐bioturbated sediment sequence libraries.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Only one previous study has assessed microbial eukaryote diversity in polychaete burrows (Engel et al ., ). Engel and colleagues () showed that ciliates and diatoms dominate A. marina burrows in non‐polluted coastal sediment. In this study, fungi dominated both H. diversicolor burrow and un‐bioturbated sediment sequence libraries.…”
Section: Resultsmentioning
confidence: 97%
“…The potential impacts of bioturbation on sediment microbial eukaryote diversity have received much less attention compared with that of bacterial diversity. In one study, 18S rRNA gene pyrosequencing of DNA isolated from Arenicola marina burrows showed that resident protist communities are different to those in un‐bioturbated sediment and at the sediment–water interface (Engel et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies demonstrated that the burrows of Nereids (H. diversicolor or Arenicola marina) harbored different eukaryotic communities compared to the un-bioturbated sediments, and more Nematodes were detected in the burrows (24,25). However, the mentioned studies mainly focused on the burrow environments; the influence of macrobenthos bioturbation on overall microeukaryotes communities in a larger scale environment has not been thus far extensively characterized.…”
Section: Introductionmentioning
confidence: 98%
“…A previous study (24) also indicated that the activities of lugworm (Arenicola marina) reduced the overall abundance of protists (mainly Cercozoa and Alveolate). The decrease of protists is probably due to the grazing/predation pressure of filter-feeding nereids, bivalves, and altered environmental conditions by macrobenthos bioturbation (28).…”
Section: Response To Macrobenthos Bioturbationmentioning
confidence: 99%
See 1 more Smart Citation